Communication from the executive of the Commonwealth, submitting an advice of Council, relative to connections with several rail roads in the state (LLMC-digital (Series), 1861)
Governor John Letcher's transmittal letter and advice of Council to the Convention. The Council advised on June 12, 1861 that propositions regarding various railroad connections should be submitted to the Convention for appropriate action.